Legal empowerment of the poor through property rights reform: Tensions and trade-offs of land registration and titling in sub-Saharan Africa - Catherine Boone (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Land registration and titling in Africa has been seen as a means of legal empowerment of the poor that can protect smallholders' and pastoralists' rights of access to land and other land-based resources. Land registration is also on the ethnojustice agenda in parts of Africa and beyond. Yet legal empowerment via registration and titling is also advocated by those who push for the market-enhancing and aggregate growth-promoting commodification of property rights, whereby market forces will transfer land out of the hands of smallholders and into the hands of 'those who can make most efficient or productive use of it'. This paper contrasts these different visions of legal empowerment, showing that each one, rather than offering a straight and clear path to pro-poor outcomes, entails powerful tensions and trade-offs. Registration and titling often have powerful redistributive implications. This helps to explain why debates over land law reform in general, and over registration and titling in particular, have been divisive in some African countries. The analysis highlights some of the broader political, institutional, and economic forces that shape the design and outcomes of land law reforms that may be undertaken (in part) to promote legal empowerment of the poor.
Keywords: K38; N57; O13; Q15; Q24; R14; 330; property; land; rights; Africa; legal empowerment; agriculture